Unstoppable - Angel, Ben (Ascent Audio, 2019)
Unlock Your Potential. Become Unstoppable. Unable to overcome debilitating fatigue and depression, bestselling author and personal development expert Ben Angel set out on a ninety-day mission to find and conquer the root of his rut. The result of his journey is Unstoppable, a highly revealing book where Ben gives you a look into the world of nootropics, wearable devices, and nutrition and delivers a guide to help you reduce stress, increase focus, improve physical performance, and eliminate your fears. You'll hear from world-leading biohackers, neuroscientists, doctors, and New York Times bestselling author Dave Asprey as Ben helps you identify the seven triggers causing your brain fog; discover the key to better health, more energy, and a better mood; optimize your mental performance and feel more alert with six nootropics; form new behaviors and break old patterns (the real secret to your success); interrupt your stress response through breathing; align your biochemistry with your soul's purpose in three easy steps; and use progressive overload to become an upgraded version of yourself. Plus, gain access to the Unstoppable Assessment to discover your identity type, pinpoint your energy levels, and create a plan to break through your own limits and become unstoppable.